Characteristics of the Hadiths About Motivation to Seek Knowledge - Idris Afandi; Ahmad Mohammad Tidjani (al-Bunyan: Interdisciplinary Journal of Qur'an and Hadith Studies, 2025)
This study aims to examine motivation in Islamic education by referring to Hadiths that discuss the importance of seeking knowledge and the characteristics of Hadiths that contain knowledge and education. Seeking knowledge is one of the obligations in Islam that is emphasized by the Prophet Muhammad SAW. Hadiths regarding the virtue of knowledge are the basis of motivation for Muslims to continue learning throughout their lives. This study uses a qualitative method with a descriptive-analytical approach, collecting related Hadiths, and conducting interpretations and analyses to explore the motivational values ​​contained therein. The results of the study show that there is intrinsic and extrinsic motivation in seeking knowledge based on Islamic teachings, where knowledge is considered a path to happiness in the world and the hereafter. The Hadiths also emphasize the importance of perseverance and sincerity in the education process, and provide inspiration to educators and students to develop their potential through knowledge. The conclusion of this study emphasizes that learning motivation in Islam is not only individual, but also has a broad social impact, where knowledge is a pillar of the progress of human civilization.